(untitled) (ModaPalavra e-periódico, 2020)
The paper investigates the origins of the construction of Carmen Miranda ́s image as the allegorical “baiana”, which has become a representative character of Brazil and of Latin America. It is based on the analysis of Carmen Miranda ́s first films in the Uni ted States produced by Twentieth Century Fox in the context of the Good Neighbor Policy, in order to discuss the underlying meanings in the image outlined in that context and that remains. It hopes that the proposed approach allows new questions and consid erations on the appropriations and manipulations of Carmen Miranda ́s image, which are still frequent when one seeks for symbols to represent Brazil.